The garden of Priapus : sexuality and aggression in Roman humor - Richlin, Amy, 1951- (Oxford University Press, 1992)
Statues of the god Priapus stood in Roman gardens to warn potential thieves that the god would rape them if they attempted to steal from him. In this book, Richlin argues that the attitude of sexual aggressiveness in defense of a bounded area serves as a model for Roman satire from Lucilius to Juvenal. Using literary, anthropological, psychological, and feminist methodologies, she suggests that aggressive sexual humor reinforces aggressive behavior on both the individual and societal levels, and that Roman satire provides an insight into Roman culture. Including a substantial and provocative new introduction, this revised edition is important not only as an in-depth study of Roman sexual satire, but also as a commentary on the effects of all humor on society and its victims.